2012
DOI: 10.1182/blood-2011-09-382390
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb group ring finger 1 cooperates with Runx1 in regulating differentiation and self-renewal of hematopoietic cells

Abstract: AbstractThe transcription factor runt-related transcription factor 1 (Runx1) is essential for the establishment of definitive hematopoiesis during embryonic development. In adult blood homeostasis, Runx1 plays a pivotal role in the maturation of lymphocytes and megakaryocytes. Furthermore, Runx1 is required for the regulation of hematopoietic stem and progenitor cells. However, how Runx1 orchestrates self-renewal and lineage choices in combination with other factors is not well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…In addition, ChIP-seq analysis of embryonic stem (ES) cells revealed that KDM2B was enriched near transcription start sites, including Hox gene loci (7). These data were consistent with the findings that DNA methylation strongly excludes the recruitment of BCOR complex components (9) and that PCGF1 regulates Hox expression (10,11).…”
Section: The Bcor Complex Is a Distinct Subtype Of Prc1supporting
confidence: 77%
See 2 more Smart Citations
“…In addition, ChIP-seq analysis of embryonic stem (ES) cells revealed that KDM2B was enriched near transcription start sites, including Hox gene loci (7). These data were consistent with the findings that DNA methylation strongly excludes the recruitment of BCOR complex components (9) and that PCGF1 regulates Hox expression (10,11).…”
Section: The Bcor Complex Is a Distinct Subtype Of Prc1supporting
confidence: 77%
“…2B); however, the prognostic value of BCORL1 mutations remains unclear. Notably, BCORL1 depletion increased the replating capacity of Runx1-depleted Lin À cells (11). These results suggest that BCORL1 dysregulation may be a cause of myeloid malignancy.…”
Section: Somatic Bcorl1 Mutations In Myeloid Malignanciesmentioning
confidence: 63%
See 1 more Smart Citation
“…Depletion of KDM2B resulted in derepression, a loss of RING1B binding and decreased H2AK119ub levels at these target genes. In mouse hematopoietic cells, PCGF1 was picked up as a factor negative regulating self-renewal of lineage negative cells in a Runx1 conditional knockout setting (Ross et al 2012). PCGF1 knockdown was shown to induce expression of HOXA cluster genes and led to a loss of H2AK119ub at the promoters of these genes.…”
Section: Pcgf Paralog Familymentioning
confidence: 99%
“…An increasing number of studies have demonstrated that the mammalian PCGFs play important roles in cell proliferation, differentiation, and tumorigenesis. For instance, PCGF1, also known as NSPc1, could promote tumor cell cycle progression and cell proliferation and also is necessary for the terminal differentiation of hematopoietic cells [7,8]. In contrast, PCGF2, also known as Mel-18, could inhibit the tumor cell proliferation and self-renewal activity of hematopoietic stem cells [9,10].…”
Section: Introductionmentioning
confidence: 99%